Physical Activity as a “Cheapest Health Tax Payment” Toward Better Health for All - Ernawati Ernawati (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
Indonesia currently faces many health-related problems, both in terms of increased morbidity and mortality due to infectious and non-communicable diseases, which stem from increasing unhealthy behaviors. The progress of science and technology is still not able to overcome this dilemma. Another problem is that actual health financing is already very good for helping communities with the existence of National Health Insurance. But over time it turned out that many obstacles appeared that could disrupt its sustainability. This becomes a serious problem that must be well thought out for the community so that people are not harmed. All of these problems arise as a result of the majority of people who have not been actively involved in prevention activities. Most of our society has behaviors that do not support health, but they engage in inactivity that is actually detrimental to health.